The effectiveness of liver function tests in the prediction of mortality in patients with COVID-19 - Erdem, Erdi Huseyin; Aydinli, Bahar; Dogru, Serkan; Ozmen, Harun (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the impact of liver function test abnormalities on mortality in critically ill coronavirus disease-2019 patients. Method: The single-centre, retrospective study was conducted at the Department of Anaesthesiology and Reanimation, Mersin City Training and Research Hospital, Turkiye, and comprised data from March 2020 to January 2022 of patients with positive real-time reverse transcription polymerase chain reaction test on nasopharyngeal swab sample for coronavirus disease-2019. Comorbidities, demographic data, admission to and discharge from the intensive care unit, Acute Physiology and Chronic Health Evaluation II scores, complete blood count on the first and second day of hospitalisation, coagulation parameters, biochemical analysis, 7-day, 28-day and total mortality of the patients in the intensive care unit were recorded. The patients were then divided into groups, with Group 1 having patients with normal liver enzymes, Group 2 having patients with abnormal liver enzymes, and Group 3 having patients with liver damage. Data was analysed using SPSS 20. Results: Of the 940 subjects, 587(62.4) were males and 353(37.6) were females. The overall mean age of the patients was 67.11±16.65 years. There were 395(42%) patients in Group 1, 534(56.8%) in Group 2 and 11(1.2%) in Group 3. Gamma-glutamyl transferase-1s, aspartate aminotransferase-2nd and albumin-2nd were significant predictors of mortality (p<0.05). Conclusion: High gamma-glutamyl transferase, aspartate aminotransferase and low albumin levels in critically ill coronavirus disease-2019 patients could be considered indicators of high mortality rate. Key Words: Coronavirus, Critical illness, Liver function test, Pandemic.